A SPRINGBOARD FOR ETERNITY - Goldblum, Kissel (Cadernos Espinosanos, 2020)
The purpose of this article is to show a way in which the human mind can reach an eternal perspective of nature. Spinoza hasexposed the possibility for our mind to understand the essence of bodies from an eternal perspective, which is not related to the present and actual existence of things. In this sense, I intend to show the importance of directing our understanding to the search for a way that surpasses the point of view of duration, so fundamental for the realization of true knowledge of Nature. Knowledge that will require something more than interpretations, signifiers and meanings. In the Theological-Political Treatise, we note that our mind, just because it contains in itself, objectively, “the nature of God and of its participation, has the power to form certain notions that explain the nature of things”. If we really want to understand Nature, we need to consider ourselves in an internal way, and not external to it. We will show that only through a non-anthropocentric analysis of the genres of Spinoza’s knowledge we can glimpse the conciliation between the essence of the Substance and the essence of the mode, and thus participate adequately in Nature. “Finally, we alsosee that reasoning is not the most important in us, but only a ladder thatallows us to rise to the desired place” (Short Traetise).